Flexural Behaviour of Reinforced Shotcrete beams Comprehending Waste Plastic Fiber - Yousif A. Mansoor; Amer M. Enad; Abdulkader I. Al-HAdithi (Wasit Journal of Engineering Sciences)
Abstract Wet-mix shotcrete is often used as a placement method in tunnelling and ground support. However, to date, only a limited number of studies have been identified the roles of waste plastic fiber (WPF) on wet-mix shotcrete mixtures. This experimental study show the flexural performance of reinforced shotcrete concrete members (beams) having waste plastic fiber, which may be considered as a new study. In order to achieve that, a manufacturing of wet-mix shotcrete machine has been developed to product special wet-mix shotcrete that will be used to cast reinforced shotcrete concrete members containing waste plastic fiber. Extensive attempts were done in this project to generate a special wet-mix shotcrete combinations using locally sourced waste materials like beverage bottles. The qualities of WPF shotcrete concrete (SC) were investigated in terms of fresh, hardened, mechanical, and bending behaviour, with extensive results analysis. Five SC formulations (0.25, 0.5, 0.75, 1.0, and 1.25) percent WPF content, as well as the control shotcrete (SC0.00), were used in the experiments. In addition, the flexural behaviour of SC beams casted from the same waste materials was investigated. The results revealed that all SC beams had almost similar flexural behaviour when compared to the creation of crack patterns, as well as the ductility index and stiffness. The maximum ductility index was 2.29 for SC0.25, while the minimum stiffness was 1.31 for SC 1.25 beam. The flexural resistance of SC beams show in beams deflection state, the primary crack with presence the waste plastic fibers was small, because of the resistance of plastic fibers to tensile stresses happening at a moment of growth the crack. It also shows that adding WPFs to SC up to (Vf=1%) results in a rise in the loads that cause initial cracks when compared to beams made with reference mix.